2021
DOI: 10.1051/0004-6361/202039867
|View full text |Cite
|
Sign up to set email alerts
|

Over-expansion of a coronal mass ejection generates sub-Alfvénic plasma conditions in the solar wind at Earth

Abstract: Context. From May 24–25, 2002, four spacecraft located in the solar wind at about 1 astronomical unit (au) measured plasma densities one to two orders of magnitude lower than usual. The density was so low that the flow became sub-Alfvénic for four hours, and the Alfvén Mach number was as low as 0.4. Consequently, the Earth lost its bow shock, and two long Alfvén wings were generated. Aims. This is one of the lowest density events ever recorded in the solar wind at 1 au, and the least documented one. Our goal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The spacecraft enters CME2 (orange region) at time t 7a , crossing another magnetic inversion line. The region after t 7b is highly sub-Alfvénic and could be caused due to the expansion of CME2 within the wake of CME1 (Chané et al 2021). This interval persists until time t 9 when PSP exits the entire ICMEperturbed plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The spacecraft enters CME2 (orange region) at time t 7a , crossing another magnetic inversion line. The region after t 7b is highly sub-Alfvénic and could be caused due to the expansion of CME2 within the wake of CME1 (Chané et al 2021). This interval persists until time t 9 when PSP exits the entire ICMEperturbed plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that several spacecraft have already observed periods of very low density in the solar wind (Lugaz et al, 2016;Chané et al, 2021;Hajra & Tsurutani, 2022). Chané et al (2021) provided an explanation of such a low density observed between May 24-25 2002 by overexpansion of an ICME during its journey to Earth.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies indicated that several spacecraft have already observed periods of very low density in the solar wind (Lugaz et al, 2016;Chané et al, 2021;Hajra & Tsurutani, 2022). Chané et al (2021) provided an explanation of such a low density observed between May 24-25 2002 by overexpansion of an ICME during its journey to Earth. Because the ICME was travelling in the wake of another CME ejected just a few hours earlier, i.e., the preceding ICME cleared away the ambient solar wind plasma and the frozen-in magnetic field, the observed over-expansion was made possible.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations